Dietary Exposure of Pacific Oyster (Crassostrea gigas) Larvae to Compromised Microalgae Results in Impaired Fitness and Microbiome Shift - Vignier, Julien; Laroche, Olivier; Rolton, Anne; Wadsworth, Pandora; Kumanan, Karthiga; Trochel, Branwen; Pochon, Xavier; King, Nick (Frontiers in Microbiology, 2021)
The Pacific oyster Crassostrea gigas is the world’s most cultivated oyster and seed supply is heavily reliant on hatchery production where recurring mass mortality events are a major constraint. Outbreaks of bacterial infection via microalgal feed are frequently implicated in these mortalities. This study assessed the effects of feeding compromised microalgae to developing oyster larvae. Intentionally ‘stressed’ (high pH) or non-stressed microalgae were fed to 11 day-old oyster larvae at two feeding rations for 96h, followed by a recovery period. Biological endpoints of larval fitness were measured following the 96h exposure and subsequent recovery. Bacterial communities associated with the microalgae feed, rearing seawater, and the oyster larvae, were characterized and correlated with effects on oyster fitness parameters. Feeding stressed algae to oyster larvae for 96h increased the occurrence of deformities (> 70% vs 20% in control), reduced feeding and swimming ability, and slowed development. Following the recovery period, fewer larvae reached pediveliger stage (2.7% vs 36% in control) and became spat (1.5% vs 6.6% in control). The quantity of stressed algae supplied to oyster larvae also influenced overall larval performance, with high feeding rations generally causing greater impairment than low rations. Bacterial profiling using 16S rRNA showed that most bacterial families characterized in larval tissue were also present in larval rearing seawater and in the microalgae feed (98%). The rearing seawater showed the highest bacterial richness compared to the larval and the microalgal compartments, regardless of feeding regime. In larval tissue, bacterial richness was highest in stressed and high-feed treatments, and negatively correlated with larval fitness parameters. These results suggest significant dysbiosis induced by compromised feed and/or increased feed ration. Several bacterial genera (e.g. Halomonas, Marinomonas) were strongly associated with impaired larval performance while the presence of genera in larvae including Vibrio was closely associated with overfeeding. Our research demonstrated that metabarcoding can be effectively used to identify microbiota features associated with larval fitness.